OPTIMIZATION OF COAL DUMP TRUCK NEEDS USING INTEGER PROGRAMMING BRANCH AND BOUND METHOD (CASE STUDY AT PT. ARUTMIN INDONESIA SENAKIN MINE, SOUTH BORNEO) - Hermawan, Danny
Indonesia is a country rich in natural resources, one of which is coal. Coal is used for the purposes of fuel power plants to the coke industry. The coal mining industry in Indonesia has undergone many developments. One of the major mining companies in Indonesia is PT. Arutmin Indonesia Senakin Mine. Mining process conducted by PT. Arutmin Indonesia Tambang Senakin uses a combination of two tools, namely Excavator and Dump Truck. The combination with the highest tool efficiency is used to achieve optimal results. One way to know the combination of Excavator with Dump Truck works well by using the match factor. The most ideal harmony factor value is the value of one, but in actual conditions the value is difficult to achieve. One of the causes arises because of the excessive use of Dump Truck, causing queues of coal hauling equipment in the mining area. Optimization needs to be done in an effort to achieve the company's daily production target with minimum cost and match factor approaching ideal. The purpose of this study is to provide recommendations on the number of optimization Dump Truck used in mining operations so as to reduce the appearance of queues. Optimization is calculated using a linear program Simplex method and advanced optimization using integer programming Branch and Bound method which generates the number of hauls in integers with minimum transport cost. Based on the research, an alternative adjustment was obtained to the number of transports to 10 units of Hino 500 FM 260 JD and 1 unit of Sany SYZ323CR-8. The combination was able to produce a harmony factor of 0,87 and achieve the company's production target of up to 300.63 tons of coal. The total cost that needs to be incurred from the combination is at least Rp 3,522,463.63 per hour.